Legal Formalism in Amendments to Mining Law in Indonesia - Suryani, Anna; Darmawan , Iwan; Satory, Agus (Universitas Kuningan, 2025)
Mining law reform is associated with the constitutional mandate of Indonesia, prioritizing social justice and welfare of the people. Therefore, this study aimed to analyze, from both philosophical and constitutional perspectives, the evolution of Indonesian mining law regulations. The analysis also aimed to examine mining law reform as a transition from legal formalism toward a just, sustainable, and participatory constitutional framework. A normative legal process with a doctrinal method was used, which was supplemented by an analysis of legal philosophy through the ontological, epistemological, and axiological dimensions of law. Data sources included statutory regulations, Constitutional Court decisions, and relevant academic literature on law and environment. The results showed that the shift in the new law generated tensions between the logic of centralization and the ideals of democratic resource management. Additionally, strengthening state control was not often accompanied by adequate checks and balances or the protection of community ecological rights. Amendments to Law on Mineral and Coal Mining produced significant philosophical and constitutional implications. As the new law reinforced state control through the centralization of authority, it simultaneously raised concerns about diminishing regional, indigenous, and public participation in natural resource governance. The importance of repositioning mining law as a constitutional instrument capable of ensuring substantive justice, ecological sustainability, and public participation was prioritized. Accordingly, the analysis recommended revising to promote inclusive participation, strengthen independent oversight, and empower the Constitutional Court to uphold the principles of social justice and right to a healthy environment.